2020
DOI: 10.1108/ijse-05-2020-0321
|View full text |Cite
|
Sign up to set email alerts
|

ICT infrastructure, innovation development and economic growth: a comparative evidence between two decades in OECD countries

Abstract: PurposeThe objective of this study is to examine the causal relationship between economic growth, information and communication technology (ICT) penetration and innovation development in OECD countries.Design/methodology/approachThis study incorporates data for 24 OECD countries from 2000 to 2018, which is divided into the earliest (2000–2009) and the latest (2010–2018) periods. The econometric methodologies of this study employ panel cointegration, estimation procedures and vector error-correction modelling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
1
4
0
2
Order By: Relevance
“…Thus, high levels of ICT improve economic growth. This result is consistent with the findings of Maneejuk and Yamaka (2020), Kurniawati (2021). In other words, the positive association between ICT and economic growth depends on the ICT infrastructure.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 92%
“…Thus, high levels of ICT improve economic growth. This result is consistent with the findings of Maneejuk and Yamaka (2020), Kurniawati (2021). In other words, the positive association between ICT and economic growth depends on the ICT infrastructure.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 92%
“…in high-impact countries, this effect is supported, which is not in middle and low-income countries. These findings are supported by Kurniawati (2020), who did research on OECD (i.e. high-income) countries and concluded that those countries had reached positive and significant economic development from high ICT penetration.…”
Section: Theoretical Backgroundmentioning
confidence: 65%
“…Although the industrial sector's technological innovation efficiency is markedly increased by informatization, its product is heterogeneous, and thus, it differs as the industry changes (Bonanno, 2016). Kurniawati's (2020) study of OECD member countries for almost 20 years shows that internet infrastructure development can enhance the level of economic growth by promoting innovation in the early years, whereas Alexander Kleibrink et al (2015) confirmed that internet infrastructure facilitates strategic performance in EU member countries. Mowery and Simcoe (2002) argued that one of the fundamental reasons the United States is leading in the internet industry is internet infrastructure development.…”
Section: Literature Reviewmentioning
confidence: 99%